2016
DOI: 10.4000/ilcea.4004
|View full text |Cite
|
Sign up to set email alerts
|

An International Survey of the Ergonomics of Professional Translation

Abstract: Sciences. We would also like to thank the anonymous reviewers for their careful reading of our article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Beneficial outcomes seem to be connected to working in-house, as both the QC editors (QC1 and QC2), who work in-house, and the in-house subtitler (FG3) reported that some on-the-job pressures they experienced were alleviated as the need for support was immediately addressed by a colleague. The beneficial potential of collegiality is reflected in Ehrensberger-Dow et al (2016), who state that the in-house translators in their study tended to have more frequent social contacts with colleagues on the job. On their end, Courtney and Phelan (2019) observe that "freelance translation is generally an unpredictable profession" (p. 105).…”
Section: Discussionmentioning
confidence: 93%
“…Beneficial outcomes seem to be connected to working in-house, as both the QC editors (QC1 and QC2), who work in-house, and the in-house subtitler (FG3) reported that some on-the-job pressures they experienced were alleviated as the need for support was immediately addressed by a colleague. The beneficial potential of collegiality is reflected in Ehrensberger-Dow et al (2016), who state that the in-house translators in their study tended to have more frequent social contacts with colleagues on the job. On their end, Courtney and Phelan (2019) observe that "freelance translation is generally an unpredictable profession" (p. 105).…”
Section: Discussionmentioning
confidence: 93%
“…This has been discussed with respect to TM (e. g. O'Brien, O'Hagan and Flanagan, 2010), postediting MT (Mesa-Lao 2014), integration of MT in TM , and the usability of tools in general (Taravella and Villeneuve 2013;Teixeira and O'Brien 2017). In the international survey mentioned above (Ehrensberger-Dow et al 2016), about three-quarters of the respondents reported that they used CAT tools and that they found them helpful at least some of the time, but most of them kept the default settings instead of customizing them to suit their needs. However, over half of those respondents said that they found certain things about their CAT tools problematic.…”
Section: Cognitive Ergonomics Of Translationmentioning
confidence: 99%
“…As discussed above, the situated activity of translation involves not only physical and cognitive aspects of the workplace but also organizational factors. The freelancers who responded to the international survey seem more isolated than the commercial and institutional translators with respect to additional resources and style guides provided by the client (Ehrensberger-Dow et al 2016). The trade-off of relative isolation is that freelancers have autonomy with respect to where, when, and how often they work; which jobs they do and in which order; and when they take their breaks.…”
Section: The Organizational Ergonomics Of Translationmentioning
confidence: 99%
“…More recently, translators' job satisfaction has been examined through ergonomic studies and affective translation psychology. With respect to the former, ergonomics, which provides insights into physical, cognitive, and organizational aspects that impinge on translations, emphasizes a connection between, on the one hand, the ergonomic conditions of the workplace, tools and resources, workflow, and organization, and, on the other hand, the productivity, health, and job satisfaction of translators (see Ehrensberger-Dow 2015Ehrensberger-Dow, Hunziker Heeb, et al 2016). With regard to the latter, Hubscher-Davidson (2016) examines the relationship between the trait "emotional intelligence" (trait EI) and job satisfaction, career success, and literary translation experience, finding some significant correlations.…”
Section: Research Contextmentioning
confidence: 99%